Possible Usage of Cannulated Pedicle Screws without Cement Augmentation - Teyfik Demir (Applied Bionics and Biomechanics)
Background: The use of pedicle screws is becoming increasingly popular for spinal surgery practice as the technology advances. Screw pullout due to bone quality and loading conditions is one of the most common problems observed after pedicle screw fixation. Several solutions were studied to prevent screw pullout. These can be investigated under three main categories: screw design, expandable screws and cement augmentation.